Antimicrobial Activity of the Leaf, Flower and Stem Extracts of Sphenoclea zeylanica - Gowri, J.; Sahayaraj, P.Arockia; Amaladasan, M (International Journal of Applied Sciences and Biotechnology, 2016)
The present study was carried out with an objective to investigate the antimicrobial potentials of leaves, flowers and stem extracts of Sphenoclea zeylanica. The aim of the study was to evaluate the antimicrobial activity and to determine the zone of inhibition of extracts against medically important bacterial and fungal strains. The antimicrobial activity was determined in the extracts using zone of inhibition method. The antibacterial and antifungal activities of extracts (40, 50, 60 and 70) of Sphenoclea zeylanica were tested against B. subtilis, P. vulgaris, S.aureus, E.coli, C. albicans, A. niger, S. typhi and B. cereus. Zone of inhibition of extracts were compared with that of control for antimicrobial activity. The results showed that the leaf extract showed notable inhibition of the microbial growth against the tested organisms. The microbial activity of the Sphenoclea zeylanic a might be due to the presence of various secondary metabolites. Hence, this plant can be used to identify the specific bioactive natural products which may serve as leads in the development of new antimicrobial agents. Int J Appl Sci Biotechnol, Vol 4(3): 325-329